2016
DOI: 10.1016/j.alcohol.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol exposure differentially effects anti-tumor immunity in females by altering dendritic cell function

Abstract: Dendritic cells (DCs) are a critical component of anti-tumor immunity due to their ability to induce a robust immune response to antigen (Ag). Alcohol was previously shown to reduce DC ability to present foreign Ag and promote pro-inflammatory responses in situations of infection and trauma. However the impact of alcohol exposure on generation of an anti-tumor response, especially in the context of generation of an immune vaccine has not been examined. In the clinic, DC vaccines are typically generated from au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…C t (threshold cycle) values were determined by the Applied Biosystems Step One Plus Real-Time PCR System. Data were analyzed by the ΔΔCT method as in [26].…”
Section: Methodsmentioning
confidence: 99%
“…C t (threshold cycle) values were determined by the Applied Biosystems Step One Plus Real-Time PCR System. Data were analyzed by the ΔΔCT method as in [26].…”
Section: Methodsmentioning
confidence: 99%
“…Alcohol may have an impact on migration of murine dermal dendritic cells to draining lymph nodes after sensitization 15. In female mice, alcohol caused a reduced dendritic function, compared to male mice 16…”
Section: General Effects Of Alcoholmentioning
confidence: 99%
“…Experimental studies in mice have revealed that alcohol-induced liver injury can lead to damage of skin barrier unction, possibly mediated via plasma TNF-α [61], whereas it has also been shown that alcohol and can influence the number and function of epidermal T cells [62] and can reduce dendritic function in female mice [63]. Moreover, alcohol can influence migration of murine dermal dendritic cells to draining lymph nodes after sensitization [64].…”
Section: Discussionmentioning
confidence: 99%